Digitalisasi Produk Siswa Melalui Cultural Storytelling: Pendampingan Pembuatan Katalog Produk Berbasis Nilai Budaya Nusantara - Vidyardi Laksmono; Exsan Adde; Irawati Irawati; Ireva Khayrani; Geary Fidya (Lembaga Pengembangan Kinerja Dosen, 2026)
This Community Service Program aimed to enhance the capacity of students at SMKS TI PGRI 11 Serpong in utilizing digital technology through a cultural storytelling approach. The program addressed students’ limited ability to integrate Indonesian cultural values into product narratives, as well as shortcomings in digital branding, information literacy, and digital security awareness. A participatory and applicative Training of Trainer (TOT) method was employed, consisting of needs assessment, training, mentoring, and evaluation. A total of 40 students participated in activities focused on cultural-based product storytelling, digital catalog development, branding strategies, information literacy, and digital security. The results showed that 85% of participants successfully created brand stories incorporating local cultural values, storytelling skills improved by 47%, digital content evaluation skills increased by 52%, and 82% of students accurately identified digital security risks. The program effectively strengthened students’ digital communication and entrepreneurial competencies while contributing to the preservation of Indonesian cultural heritage.